2011
DOI: 10.1128/jvi.05510-11
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Coreceptor Requirements for Efficient CCR5- and CXCR4-Mediated HIV-1 Entry into Macrophages

Abstract: Macrophage tropism of human immunodeficiency virus type 1 (HIV-1) is distinct from coreceptor specificity of the viral envelope glycoproteins (Env), but the virus-cell interactions that contribute to efficient HIV-1 entry into macrophages, particularly via CXCR4, are not well understood. Here, we characterized a panel of HIV-1 Envs that use CCR5 (n ‫؍‬ 14) or CXCR4 (n ‫؍‬ 6) to enter monocyte-derived macrophages (MDM) with various degrees of efficiency. Our results show that efficient CCR5-mediated MDM entry b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 85 publications
(101 reference statements)
1
36
1
Order By: Relevance
“…A number of Env substitutions have been suggested to contribute to macrophage tropism (24,25,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), but none of these suggested mutations can distinguish the paired M-tropic and T-tropic viruses used in our study. By including additional HIV-1 variants identified by intermediate CD4 usage, we observed that both MDM infection and low CD4 usage vary across a wide range.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A number of Env substitutions have been suggested to contribute to macrophage tropism (24,25,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), but none of these suggested mutations can distinguish the paired M-tropic and T-tropic viruses used in our study. By including additional HIV-1 variants identified by intermediate CD4 usage, we observed that both MDM infection and low CD4 usage vary across a wide range.…”
Section: Discussionmentioning
confidence: 76%
“…Although it is widely observed that M-tropic viruses are able to enter more efficiently at low CD4 densities (14,19,(22)(23)(24)(25)(26) and are more sensitive to neutralization by soluble CD4 (sCD4) (27)(28)(29) than T-tropic viruses, few other characteristics are widely agreed upon. Similarly, several amino acid changes in the HIV-1 Env protein have been associated with macrophage tropism (24,25,27,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), but the changes are not consistent across different subjects when macrophage tropism is defined as a distinct set of evolutionary variants within that subject (40). Furthermore, viruses isolated from the brain are sometimes referred to as neurotropic but without a clear definition of what this means phenotypically other than being located in the central nervous system (CNS) at the time of isolation.…”
mentioning
confidence: 99%
“…Single round entry assays were conducted in NP2-CD4 cells expressing either wild type (WT) CCR5 or CCR5 containing various mutations in the N-terminal region using Env-pseudotyped luciferase reporter viruses, in the presence or absence of MVC (Figure 5). The levels of virus entry in cells expressing CCR5 mutants were expressed as percentages of that attained in cells expressing equivalent levels of WT CCR5, which was verified by flow cytometry as described previously [62,64,65] (data not shown). In the absence of MVC, both 17-Res and 24-Res Envs displayed significantly increased dependence on Tyr10, Tyr14 and Tyr15 residues in the CCR5 N-terminus, which are known to be sulfated in vivo , compared to their MVC-sensitive parental strains.…”
Section: Resultsmentioning
confidence: 99%
“… a Musich et al (2011) b Cashin et al (2011) c Dunfee et al (2006) d Duenas-Decamp et al (2009) e Thomas et al (2007) f Duenas-Decamp et al (2008) g Dunfee et al (2007) h Ouyang et al (2014) …”
Section: Figmentioning
confidence: 99%